2016
DOI: 10.3168/jds.2016-10904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whey, milk, and delactosed permeates as salt substitutes

Abstract: Whey and milk permeates are by-products of high-protein dairy powder manufacture. Previous work has shown that these permeates contribute to salty taste without contributing significantly to sodium content. The objective of this study was to explore the sensory characteristics and compositional analysis of permeates from different milk and whey streams and a low-sodium product application made from them. Skim milk, Cheddar, cottage, and Mozzarella cheese whey permeates were manufactured in triplicate, and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
0
26
0
6
Order By: Relevance
“…Dietary information obtained from Malawian infants during the period of complementary feeding was used to generate a representative diet consisting of eight principal ingredients [M8 (17)]. S-BMO was obtained from de-lactosed permeate, a dairy ingredient developed as a coproduct of whey protein isolation; deproteinization and removal of lactose was achieved by ultrafiltration and diafiltration (22). Mass spectrometry of the resulting oligosaccharide-enriched fraction established that it was composed primarily of 3′-sialyllactose and 6′-sialyllactose (88% of the oligosaccharide content), with the remaining structures consisting of neutral trihexoses of glucose, galactose, and N -acetyl-glucosamine-galactosamine and longer neutral oligosaccharides (see ref.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary information obtained from Malawian infants during the period of complementary feeding was used to generate a representative diet consisting of eight principal ingredients [M8 (17)]. S-BMO was obtained from de-lactosed permeate, a dairy ingredient developed as a coproduct of whey protein isolation; deproteinization and removal of lactose was achieved by ultrafiltration and diafiltration (22). Mass spectrometry of the resulting oligosaccharide-enriched fraction established that it was composed primarily of 3′-sialyllactose and 6′-sialyllactose (88% of the oligosaccharide content), with the remaining structures consisting of neutral trihexoses of glucose, galactose, and N -acetyl-glucosamine-galactosamine and longer neutral oligosaccharides (see ref.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium and potassium, the largest contributors to salty taste, are found in milk at concentrations of 391 to 644 and 1,212 to 1,681 mg/kg, respectively (Gaucheron, 2005). Milk permeate has a salty taste intensity on par with that of Cheddar whey-less than that of cottage cheese whey permeates, Mozzarella whey permeates, or delactosed permeates but still clearly detectable (Smith et al, 2016). Li et al (2015b) added lactose-hydrolyzed whey permeates to chocolate milk to increase the sweetness of the milk but found that the increase in saltiness that resulted from the permeate minerals was too intense to make this a viable alternative sweetening method.…”
Section: Macronutrient Componentsmentioning
confidence: 99%
“…Due to its mineral content of 9–10 g/100 g dry matter and salty flavour, DLP is effective in reducing the level of sodium in formulated food products while retaining sensory acceptability (Dixon, ; Burrington et al ., ; Smith et al ., ). In these studies, it was shown that the replacement ratio for DLP is roughly ~3 g for 1 g of sodium chloride (NaCl), to achieve similar sensory characteristics as NaCl.…”
Section: Future Applications Of Delactosed Permeatementioning
confidence: 97%
“…Therefore, DLP can also be regarded as a valuable mineral source in addition to lactose and other minor components, such as organic acids and oligosaccharides. Moreover, the considerable concentration of calcium, potassium and magnesium in DLP can (i) enhance the nutritional profile of many foods, (ii) act as a salt substitute (Smith et al ., ) or (iii) be used to some extent as a functional ingredient in combination with whey protein phospholipid concentrate in the manufacture of bakery and confectionery products (Levin et al ., ).…”
Section: Introductionmentioning
confidence: 99%